Creating the Image of a Safe City: Reduction of Visible Violence in Rio de Janeiro - Saborío, Sebastían (2017)
Recently, a new policy of public security has been instated in Rio de Janeiro, aiming for the pacification of the “favelas”. This policy gives control to the UPP (Pacifying Police Units) of some favelas occupied by heavily armed groups. This article shows that, contrary to what local institutions declare, the pacification processes in the favelas do not actually seek “bringing peace” to these urban territories characterized by a high index of violence. In this article, it is argued that the UPPs are part of a bigger strategy which aims to reduce the visibility of violence, and, as a result, the common perception of Rio de Janeiro as a dangerous city.